2011
DOI: 10.1108/17410391111122844
|View full text |Cite
|
Sign up to set email alerts
|

Framework for selecting an appropriate e‐business model in managerial holding companies

Abstract: Purpose-The main aim of the present study is to propose a framework for selecting an appropriate electronic business (e-business) model in managerial holding companies with a chain structure acting in the area of the automobile industry. Design/methodology/approach-This is an applied study conducted as a survey and case study. First, the factors affecting selection of an appropriate e-business model in managerial holding companies with chain structure in auto industry are identified through a survey and by tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Then the methodology as a case study in Sazeh Gostar Saipa Company has been studied and examined. It is noteworthy that Saipa Company alongside Iran Khodro Company has the largest market share in Iran (Hanafizadeh & Shafiei Nikabadi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Then the methodology as a case study in Sazeh Gostar Saipa Company has been studied and examined. It is noteworthy that Saipa Company alongside Iran Khodro Company has the largest market share in Iran (Hanafizadeh & Shafiei Nikabadi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Noudoosbeni et al (2010) conclude that uprating professional competencies through appropriate training is a key component of successful IS project implementation, and that lack of planning and management as well as inadequate training led to IS project failure in their specific area of study (Malaysian companies). In Iran, a range of issues has hampered IS deployment in the country -lack of managerial skills, low IT maturity, poor training, poor internet access, governmental policies, and poor business planning (Shahin et al, 2010;Hanifzade & Nikabadi, 2010;Amid et al, 2011). Other researchers (Dixit & Prakesh, 2011) have suggested that the lack of human capability and economic conditions in developing countries lead to IS failure and prevent overall economic growth.…”
Section: Erp In Developing World Contextsmentioning
confidence: 99%
“…Supply chain of Iran Khodro Co. consists of subsidiaries which include designing and engineering companies (like Taam Iran Khodro), suppliers (like SAPCO), manufacturer (like Iran Khodro Industrial Group) and after-sales services (like ISACO), and in this way, Iran Khodro Co. has formed a supply chain, on which it has control and supervision. In addition, the supply chain of Saipa Co. consists of subsidiaries which include designing, engineering companies and suppliers (like SazehGostar), manufacturer (like Saipa Industrial Group) and after-sales services (like Emdad Khodro), and in this way, Saipa Co. has formed a supply chain, on which it has control and supervision (Hanafizadeh and Shafiei Nikabadii, 2011;Shafiei Nikabadii and Zamanloo, 2012). VINE 44,3…”
Section: Case Study: Supply Chain Of Automobile Industry In Iranmentioning
confidence: 99%